Transisi PSAK 24 ke PSAK 219: Potret Implementasi Akuntansi Imbalan Kerja Tenaga Panen - Hamimah; Marliza Noor Hayatie; Try Edi Suwarno; Rahmatullah Alfikri (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to analyze the implementation of harvest workers’ wage accounting at PT XYZ based on PSAK 219 on Employee Benefits, following its adoption as an update and new nomenclature of PSAK 24. The focus is on recognizing and measuring harvest workers’ wages as short-term employee benefits, which are vital to company operations. The research applies a qualitative descriptive approach with data collected through observation, interviews, and documentation. Results indicate that PT XYZ uses a performance-based wage system (pure piece rate) for harvest workers, complemented by premiums and incentives. The income tax of harvest workers is recognized as an allowance under the gross-up principle. Wage recognition and measurement follow PSAK 219, recorded as liabilities and expenses after services are rendered, while considering mandatory deductions such as BPJS. However, the treatment of overpayments has not fully complied with PSAK 219. This research contributes to the development of internal accounting information systems for plantation companies in ensuring the accuracy of accrual expenses and wage transparency, while also serving as an empirical reference for the transition of employee benefit standards in Indonesia.